The Aestheticization of Saung as a Sundanese Cultural Resilience Space - Edwin Widia; Sunarmi; Siti Badriyah (Publikasi Indonesia, 2026)
This article theorizes the aestheticization of Saung, a traditional Sundanese shelter, as a strategy of cultural resilience rather than commodification. The research examines how the Saung is experienced, negotiated, and transformed by diverse social actors in contemporary Sundanese restaurants. Drawing on phenomenology, constructivism, and Bourdieu’s theory of practice, the research utilizes a quadrant model of design processes and a matrix of actor intentions. The research demonstrates that the Saung operates as an allegorical and affective space where embodied feeling (rarasaan), symbolic representation, material ecology, and adaptive design converge. Aestheticization is theorized here as counter-reification, a process through which tradition proliferates without becoming fixed. The article advances a second, theoretically distinct analysis by shifting the focus toward the mechanisms through which vernacular space endures. It argues that resilience is achieved through transversion, understood as the adaptive re-materialization of cultural codes, and through embodied affect that sustains cultural coherence amid contextual transformation.